(untitled) (MAUSAM, 1965)
M2 or first shear mode continental Rayleigh waves excited by the Russian nuclear explosion are studied with reference to the continental structure. There is general agreement with crustal thickness of 45 km. The other aspects of the dispersion curve are also discussed with reference to previous works by others.